Prevalence and predictors of antibiotic prescription errors in an emergency department, Central Saudi Arabia - Alanazi, Menyfah Q. (2015)
Background Inappropriate antibiotic (ATB) prescriptions are a threat to patients, leading to adverse drug reactions, bacterial resistance, and subsequently, elevated hospital costs. Our aim was to evaluate ATB prescriptions in an emergency department of a tertiary care facility... Methods A cross-sectional study was conducted by reviewing charts of patients complaining of infections. Patient characteristics (age, sex, weight, allergy, infection type) and prescription characteristics (class, dose, frequency, duration) were evaluated for appropriateness based on the AHFS Drug Information and the Drug Information Handbook. Descriptive and analytic statistics were applied.